PENGARUH KARAKTERISTIK PEKERJAAN DAN KOMITMEN ORGANISASI TERHADAP MOTIVASI SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI JAMBI. - Dessy Jusfartinah; Tetty Asnawi; Arna Suryani (Universitas Batanghari, 2017)
The purpose of this research is to gain an overview of karakeristik of work, organizational commitment, motivation and performance of employees at the Department ofmarine and Fisheries province of Jambi and to know the influence of characteristicsof work and commitment the Organization's response to the employee motivation and performance, as well as to know the influence of motivation on performance. To address the research objectives then requires the author studies the theory related to the variable of research i.e. the theory of characteristics of work, organizational commitment, motivation and performance. In addition the author also searched for relevant earlier research in the form of articles/journals and previous thesis to supportthis research. The population in this research is the Department of Marine and fisheries officer province of Jambi that add up to 57 employees. Due to the number of population in this study less than 100 people then in this research sampling method using the method of census. Analysis techniques using path analysis to see the direct and indirect influence, and was succeeded by testing RSquare and hypothesis testing partially and simultaneous with t-test and F-test of the test path analysis is done, the results Research shows that the characteristics of the work and the commitment of the Organization to have an impact on the motivation and performance of employees. Where on the basis of the results of the test t (partial) and F (Simultaneous) tests showed that the characteristics of the work and the commitment of the Organization had a significant and positive influence towards motivation and performance, so did motivasijuga have influence significant and positive on performance. This explains that the characteristics of the work and commitment of organizations that either have a positive influence in providing and enhancing motivation to work-have implications for improved performance against employees at the Department of marine and Fisheries The Province Of Jambi. This research makes some conclusions based on the results of research of characteristics of work, organizational commitment, motivation and performance of employees at the Department of marine and Fisheries province of Jambi in good enough conditions, characteristics the work and the commitment of the Organization a positive and significant effect against the motivation of working either partially or simultaneously, the characteristics of the job and the Organization's commitment to a positive and significant effect on performance of goodemployees partially or simultaneously, work motivation affects employee performance, and the characteristics of the work and commitment of organizations collectivelythrough motivation can direct and indirect effect against against performance employees at the Department of marine and Fisheries province of Jambi.Keywords: organizational commitment, Job Characteristics, Motivasidan performance.